Impact of large investors on firm dividend policy - Zandi Pour Joopari, GholamReza; Shahabi, Alireza; Naysary, Babak (2013)
Block holders have significant impacts on the firm’s policies, especially strategies regarding the payout policy. The purpose of this study is to investigate the relationship between ownership structure and firm dividend policy considering the role of block investors in the companies listed in TSE. We selected 37 public listed companies with state block holders and match them with almost similar companies with non-state block holders in 2012. Running a multiple regression, we found that there is a positive relationship between both types of block holders and firm’s dividend policy. These results support the tax-based hypothesis.